PENGARUH ALKOHOL TERHADAP PENURUNAN BERAT CEREBELLUM PADA TIKUS WISTAR REMAJA - Suryanti Suryanti (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background. Alcohol is a depressant substances that damage the body'sorgans. One of the organs that are vulnerable to alcohol consumption , namelythe cerebellum . Consumption of alcohol will damage the cerebellum and lowerdensity of Purkinje cells thereby reducing the weight of the cerebellum . Alcoholalso mehambat activity of insulin- like growth factor receptor (IGF ) I, which aregrowth factors and cell proliferation.Methods. The purpose of this study was to determine the effect of alcohol onweight loss cerebellum . This type of research is the study of pureexperimentation with the design of post-test only control group design todetermine the weight of the cerebellum .Result and Conclusion. Results of this study are in the group of rats that weregiven alcohol weight loss than the control group . Analysis cerebellum weightbetween groups with multiple comparasion showed that there were significantdifferences ( p < 0.05 ) between group B and group A.Keyword : Cerebellum, Alkohol